Assessment of Selected Health Determinants among Almajiri Students in Gwadabawa Local Government, Sokoto State, Nigeria - Y. Sarkingobir; M.S. Nahantsi; Z. Shehu; A.A. Sadiq; N. Malami; A. Saadu; A. Hamza (Journal of Applied Sciences and Environmental Management, 2019)
Health determinants are factors that can influence our health either positively or negatively. This paper determined the factors that affect the health of Almajiri in their system of study in Gwadabawa local government of Sokoto state, Nigeria. Interview and visual observation were used to collect data, which was analyzed by thematic networks method. The result of this study was shown. Most (50.0%) of the Almajiri live in buildings own by school,whereas, 33.5% of them in donated buildings .There were three types of houses / classes where Almajiri live.Most (50.0%) were made of cement/modern style ,then (33.3%) the mud houses / classes, and (16.7%) were the ones from zinc .There were toilets for urination only ,no one was slated for defecation . In 75% of the schools there was no water, whereas 33.3% have water source from unprotected wells. In 33.3 % of the schools there was refuse dumps .In 33.3% there were no any source of risk. Whereas, in 16.7% there were gutters, and in 16.7% there were roads nearby. Personal hygiene was observed. 75.0% of Almajiri wore dirty garments.25.0% wore cleaned garments, 12.5% wore torn garments, and 87.5% wore untorn garments. 62.5% wore shoes and 37.5% have no shoes. 62.5% take bath weekly, 37.7% take bath daily. Interms of livelihood, most of them relied on begging for food; 25.0% do domestic work to get food and other needs. 70.0% of them eat twice in a day, 25.0% thrice, whereas, 5.0% once; in most cases. The result revealed many health determinants which can negatively affect the health of Almajiri.